Materiales didácticos y su influencia en los procesos de enseñanza aprendizaje en los estudiantes de la UE Juan León Mera, Montalvo. 2022 - Yanchaliquin Bonilla, Angelle Yulissa (2023)
Education today is one of the fundamental elements, therefore it is of the utmost importance that in educational institutions the teacher integrates didactic materials in the different subjects in order to improve the teaching-learning process of the students, since the students of the EU Juan León Mera of the Montalvo canton to which There is an insufficiency in their teaching-learning processes due to the little use of didactic materials. Through this research, it is carried out with the purpose of the benefits that students will have at the moment in which the teacher begins to integrate the didactic materials in the different areas, in order to improve their knowledge and develop significant learning in each student, learn to work from cooperative way within the groups of students, improving the interrelation between them. The use of didactic materials is very important, it allows to obtain a good relationship between the student and the teacher who guides and influences them in the development of skills and knowledge, since it fosters a pleasant environment and in turn builds learning significant in the students within the classroom and also to participate actively, obtaining as a result a quality education, that is why it is necessary that the appropriate techniques must be applied.